ALIH KODE DAN CAMPUR KODE DALAM PERCAKAPAN ANTARSISWA SMA NEGERI 1 SUTI SEMARANG KABUPATEN BENGKAYANG - Asista, Vera; Madeten, Sisilya Saman; Amir, Amriani (Universitas Tanjungpura, 2025)
This study examines the phenomenon of code-switching and code-mixing in the conversations of students at SMA Negeri 1 Suti Semarang, Bengkayang Regency. The background of this research lies in the multilingual environment of the school, where students use various local languages, including Dayak Bakati Sebiha, Bemoyok, and Malay, alongside Indonesian. The study employed a qualitative descriptive approach with data obtained through observation and note-taking of students